Local Snack Innovation in the Arrendi Home Industry Through Product Diversification and Modern Packaging in Mataram - Titin Windiasari; Sari Novida; Baiq Inggar Linggarweni (Unram Journal of Community Service, 2026)
Product innovation is an effort to increase sales value and business profits that can be done in several ways such as product diversification and packaging innovation. Product diversification carried out on target partners is by providing innovative flavor and shape variants in the various chips produced and packaging the products well. The resulting products must be adapted to current consumer tastes. The purpose of this activity is to provide knowledge, skills and assistance to target partners on product diversification through diversification of flavor and shape variants, packaging innovation so that it can become consumer attraction. The target partner is the Arrendi home industry. The activity methods are: (1) socialization; (2) training; (3) monitoring and evaluation; (4) program sustainability. The results of the activity are that 100% of target partners are satisfied with the activities carried out by the implementation team, 82% of partners are able to operate the tools provided, 85% of partners know about product diversification and packaging. The outputs produced in this activity are various chips with flavor variants and modern packaging, journals, activity videos, IPR.